The Implementation Of Tooth-Filing (Potong Gigi) Ceremony During Nyekah - Ni Gusti Ayu Agung Nerawati (Kamaya: Jurnal Ilmu Agama, 2021)
Tooth-Filing (Potong Gigi) ceremony is one of the most important ceremonies and it must always be carried out because it contains the moral values needed to become a suputra child. Tooth-Filing ceremony during Nyekah was held in one resident’s house, which was at the original house or Merajan Gede. Thus, this ceremony can only be carried out by large families who are still tied to one Merajan Gede. Tooth-Filing ceremony during Nyekah is unique, in which Tooth-Filing ceremony is usually carried out independently or along with the Manusa Yadnya ceremony, such as marriage. However, Tooth-Filing ceremony is held during Nyekah ceremony, where this ceremony is included in the Pitra Yadnya ceremony. Besides, the uniqueness also appears during the implementation of Tooth-Filing ceremony. This ceremony was witnessed by Bhatara Lingga and Dewa Hyang from Sawa who had been clean.